2002
DOI: 10.1053/joca.2002.0815
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intraarticular hyaluronic acid in patients with osteoarthritis—a prospective clinical trial

Abstract: This controlled prospective clinical trial confirmed that 5 weekly intraarticular injections of HA (Hyalart) in patients with OA of the knee provide pain relief and functional improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 33 publications
0
32
1
2
Order By: Relevance
“…23 The estimated total hyaluronic acid in a human knee joint is from 4-8 mg. 23 Intra-articular injections of hyaluronic acid with a molecular weight between 500 and 750 kilodaltons (kD) have been studied using corticosteroid injections [24][25][26][27][28] or NSAIDs 29 as control treatment, and by conducting placebo controlled clinical trials. [30][31][32][33][34][35][36][37] These studies suggested that intra-articular injection of hyaluronic acid may improve the clinical condition and have a long term beneficial effect in knee osteoarthritis patients especially if osteoarthritis was less than moderate in grade. [30][31][32][33][34][35][36][37] A review by Maheu looked at five different clinical trials, comparing different regimens of Hyalgan (a hyaluronan preparation; Sanofi-Synthelabo) versus corticosteroid injections in the osteoarthritis knee, with follow ups from 2-12 months.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…23 The estimated total hyaluronic acid in a human knee joint is from 4-8 mg. 23 Intra-articular injections of hyaluronic acid with a molecular weight between 500 and 750 kilodaltons (kD) have been studied using corticosteroid injections [24][25][26][27][28] or NSAIDs 29 as control treatment, and by conducting placebo controlled clinical trials. [30][31][32][33][34][35][36][37] These studies suggested that intra-articular injection of hyaluronic acid may improve the clinical condition and have a long term beneficial effect in knee osteoarthritis patients especially if osteoarthritis was less than moderate in grade. [30][31][32][33][34][35][36][37] A review by Maheu looked at five different clinical trials, comparing different regimens of Hyalgan (a hyaluronan preparation; Sanofi-Synthelabo) versus corticosteroid injections in the osteoarthritis knee, with follow ups from 2-12 months.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37] These studies suggested that intra-articular injection of hyaluronic acid may improve the clinical condition and have a long term beneficial effect in knee osteoarthritis patients especially if osteoarthritis was less than moderate in grade. [30][31][32][33][34][35][36][37] A review by Maheu looked at five different clinical trials, comparing different regimens of Hyalgan (a hyaluronan preparation; Sanofi-Synthelabo) versus corticosteroid injections in the osteoarthritis knee, with follow ups from 2-12 months. 38 One study showed initial superiority of Hyalgan over corticosteroid injections and in three studies, equal efficacy over time.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…These agents are usually administered as a series of 3-5 weekly injections, but recent data suggests a single 6 ml injection of the agent hylan-GF 20(SynviscTM) may be effective as well [66]. There is great heterogeneity in existing trials of these agents, making strong conclusions as to their efficacy difficult, with many studies of small size and varying quality [67,68]. A systematic review assessing the efficacy of HA analyzed 76 blinded RCTs evaluating multiple HA agents.…”
Section: Hyaluronic Acid (Ha)mentioning
confidence: 99%
“…A review by Maheu looked at 5 different clinical trials, comparing different regimens of Hyalgan versus corticosteroids injections in osteoarthritis knee, with follow ups from 2-12 mths. [12][13][14][15] One study showed initial superiority of Hyalgan and in three studies equal efficacy over time. The fifth study used a combination of Hyalgan and corticosteroid injections initially.…”
Section: Introductionmentioning
confidence: 99%